A positive analysis of targeted employment protection legislation - Juan José Dolado; Marcel Jansen; Juan F. Jimeno (Institute for the Study of Labor (IZA), 2007)
In many countries, Employment Protection Legislation (EPL) establishes less strict dismissal procedures for specific groups of workers. This paper builds a simple matching model with heterogeneous workers in order to analyze this feature of EPL. We use the model to analyze the effects of reforms targeted at lowering the firing costs of a particular group of workers, and compare the results with those stemming from a comprehensive reform that reduces firing costs for all workers. The model is calibrated for the Spanish economy, where an important reform of this kind took place in 1997. Overall, our results point out that EPL reforms achieve the largest reduction in unemployment when they are targeted to workers with lower and more volatile productivity.
urn:nbn:de:101:1-20080414115
Keywords: 330; Kündigungsschutz; Deregulierung; Arbeitsproduktivität; Wirkungsanalyse; Beschäftigungseffekt; Spanien